Multifaceted intervention including Facebook‐groups to improve guideline‐adherence in ICU: A quasi‐experimental interrupted time series study. Issue 10 (19th August 2021) - Petosic, Antonija; Småstuen, Milada C.; Beeckman, Dimitri; Flaatten, Hans; Sunde, Kjetil; Wøien, Hilde
Abstract: Background: The impact of social media, with its speed, reach and accessibility, in interventions aimed to improve adherence to guidelines such as assessment of Pain, Agitation/Sedation and Delirium (PAD) in intensive care is not described. Therefore, the primary objective of this quality improvement study was to evaluate the impact of a multifaceted intervention including audit and feedback of quality indicators (QI) via Facebook‐groups, educational events and engagement of opinion leaders on adherence to PAD‐guidelines in four ICUs. Methods: A quasi‐experimental interrupted time series study with eight monthly data points in the two phases Before and Intervention was designed. Proportion of nursing shifts with documented PAD‐assessment (PAD‐QIs) were retrieved from the electronical medical chart from included adult ICU patient‐stays in four participating ICUs. Difference between the two time periods was assessed using generalised mixed model for repeated measures with unstructured covariance matrix, and presented as Beta (B) with 95% confidence interval (CI). Results: Finally, 1049 ICU patient‐stays were analysed; 534 in Before and 515 in Intervention. All three PAD‐QIs significantly increased in Intervention by 31% (B = 30.7, 95%CI [25.7 to 35.8]), 26% (B = 25.8, 95%CI [19.4 to 32.2]) and 34% (B = 33.9, 95%CI [28.4 to 39.4]) in pain, agitation/sedation and delirium, respectively. Conclusion: A multifaceted intervention including use of Facebook‐groups was associated with improved guideline‐adherence in four ICUs, as measured with process PAD‐QIs of PAD assessment. Further research on use of social media to improve guideline adherence is warranted, particularly as social distancing impacts clinical education and training and new approaches are needed.